Sintesis ZSM-5 dari Fly Ash Sawit Sebagai Sumber Silika dengan Variasi Nisbah Molar Si/Al dan Temperatur Sintesis - Ida Zahrina; Yelmida Yelmida; Fajril Akbar (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Palm fly ash is biomass/waste in the  palm oil industry. Palm fly ash has high content of amorphous silica. ZSM-5 is one of synthetic zeolite which is widely used as catalyst in industries. ZSM-5 has high activity and selectivity to several hydrocarbon conversion reaction. Hence, ZSM-5 is being investigated for the conversion of vegetable oil to hydrocarbon.  It can be synthesized from silica and alumina. Sources of silica that can be added to the ZSM-5 synthesis,  are sodium silicate, hydrated silica, water glass sol silica, gelled silica, clay, precipitated silicaand calcined silica. ZSM-5 was synthesized free-template by using palm fly ash as silica source. In this research synthesis of ZSM-5 was carried out in autoclave at 18 hours and Na2O/Al2O3 molar ratio by various molar ratio from 30 to 40 and temperature in the range of 150 to 190 oC. The product was then analized using FTIR method. The best ZSM-5 product was obtained at Si/Al molar ratio of 40 and process temperature of 150 oC.